2007
DOI: 10.1093/aob/mcl215
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Land-use Change on Plant Traits, Communities and Ecosystem Functioning in Grasslands: A Standardized Methodology and Lessons from an Application to 11 European Sites

Abstract: This work shows the applicability of a set of protocols that can be widely applied to assess the impacts of global change drivers on species, communities and ecosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
409
1
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(428 citation statements)
references
References 63 publications
9
409
1
9
Order By: Relevance
“…Recent reviews have stressed the need for integrated efforts in studying emerging properties of plant traits on lower hierarchical levels of the plant individual and their scaling up at higher organizational levels of the population, community and the entire ecosystem (Sammul et al 2008). The analysis of clonal growth attributes at the scale of plant assemblages can make a contribution in this direction, because it is the relative composition and diversity (Wright et al 2006) of traits associated with ecological functions that can be scaled up to predict ecosystem functions (Reich et al 1992;Díaz and Cabido 2001;Garnier et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews have stressed the need for integrated efforts in studying emerging properties of plant traits on lower hierarchical levels of the plant individual and their scaling up at higher organizational levels of the population, community and the entire ecosystem (Sammul et al 2008). The analysis of clonal growth attributes at the scale of plant assemblages can make a contribution in this direction, because it is the relative composition and diversity (Wright et al 2006) of traits associated with ecological functions that can be scaled up to predict ecosystem functions (Reich et al 1992;Díaz and Cabido 2001;Garnier et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…100), despite substantial differences in stem anatomy among botanical families 244 , including those between non-monocotyledons and monocotyledons (where sheaths were measured). We used a data set of 422 herbaceous species collected in the field across Europe and Israel, and belonging to 31 botanical families 144 to parameterize linear relationships of StDMC to LDMC. The slopes of the relationship were significantly higher for monocotyledons than for other angiosperms (F = 12.3; P < 0.001); within non-monocotyledons, the slope for Leguminosae was higher than that for species from other families.…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, we showed that Ecobordure is efficient in revealing potential causes of the observed vegetation patterns. For grassland communities, it has been shown that ecological characteristics of plant species help to distinguish between differing land-use disturbance (Garnier et al, 2007). Based upon three complementary species groups with contrasted ecological requirements, Ecobordure can reveal a wide range of potential drivers but also aspects sometimes counter-intuitive.…”
Section: Discussionmentioning
confidence: 99%